Analysis of Images, Social Networks and Texts 4th International Conference, AIST 2015, Yekaterinburg, Russia, April 9-11, 2015, Revised Selected Papers - Khachay, Mikhail Yu; Konstantinova, Natalia; Panchenko, Alexander; Ignatov, Dmitry; Labunets, Valeri G. (Communications in Computer and Information Science, 2015)
This book constitutes the proceedings of the Fourth International Conference on Analysis of Images, Social Networks and Texts, AIST 2015, held in Yekaterinburg, Russia, in April 2015. The 24 full and 8 short papers were carefully reviewed and selected from 140 submissions. The papers are organized in topical sections on analysis of images and videos; pattern recognition and machine learning; social network analysis; text mining and natural language processing.     .